Pandemic-Related Stress Symptoms Among Norwegian Parents of Adolescents in Grades 6 to 8 - Idsoe, Thormod; Dyregrov, Atle; Janson, Harald; Nærde, Ane (Frontiers in Psychiatry, 2021)
We investigated pandemic-related stress symptoms during the first COVID-19 lockdown period in spring 2020 among parents of adolescents that were 11 to 13 years old in the study period. We also investigated whether parental stress symptoms were associated with family situation and family activities during lockdown. Altogether 147 couples reported about their own trauma-related stress symptoms following the outbreak of the pandemic. Among the respondents, 9.5% of the mothers and 10.2% of the fathers had scores over cutoff on the screener (IES-6) measuring stress symptoms, a non-significant gender difference. Scores on the screener were not associated with family contamination or lockdown consequences. Family activities during lockdown did not impact the pandemic stress symptom levels. Whereas, the experience of the COVID-19 pandemic pose a stressor to most people, it is unlikely to be a criterion A event for other than directly affected families.